The Role of the Elections Supervisory Agency to Contend Hoax and Hate Speech in the Course of 2019 Indonesian General Election - Fritz Edward Siregar (PADJADJARAN Jurnal Ilmu Hukum (Journal of Law), 2020)
AbstractThe Elections Supervisory Agency, in Indonesia known as Bawaslu (Badan Pengawas Pemilu), is the supervisor for all elections in Indonesia. The Agency has many roles, authorities, and obligations. One of their authorities is to oversee the activities of campaigns in various platforms, including the social media. The Agency has an authority to ensure and to keep the election participants not to violate campaign rules. They are obliged to ensure no misuse of social media, considering that the social media has been platforms to spread hoaxes and hate speeches–activities that can disrupt and undermine the ongoing democratic process. This study aims to explain the achievements of Bawaslu in carrying out the process of monitoring social media, the obstacles, the findings, the enforcements, and the importance of the role of state institutions. Prior to the prosecution, such as taking down media content, account deletion, or criminal prosecution, it is necessary to pay attention to the existing legal rules. This study performed analysis employing qualitative method with juridical-empirical approach. The data consisted of the spread of hoaxes and hate speeches that are spread on social media during the course of the 2019 Election stages. Peran Badan Pengawas Pemilu Menangani Berita Bohong dan Ujaran Kebencian dalam Pemilu 2019Abstrak Dalam kedudukannya sebagai pengawas pemilu, Badan Pengawas Pemilu (Bawaslu) tidak sekadar berwenang untuk mengawasi pelaksanaan kampanye melalui media sosial oleh para peserta pemilu untuk tidak melanggar aturan kampanye. Bawaslu berkewajiban memastikan agar tidak ada penyalahgunaan media sosial dengan berita bohong (hoax) dan ujaran kebencian (hate speech), yang dapat menganggu dan merusak proses demokrasi yang berlangsung. Akan tetapi pengawasan di media sosial memiliki persoalan tersendiri karena dibutuhkan keseimbangan antara pembatasan kebebasan berbicara dan aturan mengenai ujaran kebencian. Artikel ini berusaha untuk menjelaskan, apa saja yang sudah dilakukan oleh Bawaslu dalam melakukan proses pengawasan di media sosial, hambatan yang dialami, temuan yang ditindak lanjutin dan pentingnya peran antar lembaga negara. Sebelum dilakukan proses penindakan baik penurunan konten, penghapusan akun serta proses pidana, perlunya memperhatikan aturan hukum yang ada. Analisa dalam tulisan ini ditulis berdasarkan kajian kualitatif dengan pendekatan yuridis-empiris dan penyebaran isu kebohongan dan ujaran kebencian yang ada di media sosial selama proses pemilu 2019 berlangsung.Kata kunci: hoaks dan ujaran kebencian, kebebasan berbicara, pengawasan pemilu. DOI: https://doi.org/10.22304/pjih.v7n2.a2